Percepção de acadêmicos de enfermagem sobre a importância da religiosidade e da espiritualidade na cura ou sobrevida de pacientes graves - JESUS, Mariana Gurjão de (2019)
Introduction: One of the most important tools that the human being found to deal with their suffering is religious faith and spirituality, which have always been present in their daily lives, even in modern times. There is scientific evidence that religion and spirituality have a positive influence on people's health, however, many nursing students do not consider themselves adequately prepared to address these issues in practice. Objectives: To understand the perception and the meaning attributed by the nursing student to religion and spirituality in the treatment of serious illness and the importance of addressing assistance to the spiritual dimension of the patient along the graduation. Methodology: An exploratory study, cross-sectional, qualitative study conducted with twelve students of the Nursing School of the Federal University of Pará, the method used for data collection it was a semi-structured interview with eight open questions, the data were analyzed according to the proposed method by Bardin, the study met the requirements of Resolution 466/2012 approved by the ethics committee of the faculty itself. Results: The categories resulting from the present study interviews constituted four dimensions related to the research objectives. Conclusion: Spirituality and religiosity have been recognized by all participants of research as an integral and important part of nursing care, therefore, the inclusion of this subject in the curricula of undergraduate programs in nursing is necessary in order to offer subsidies for students and future professionals.